HISTORICITY OF SANAD HADITH THEORY: An Epistemological Review - Kamridah, Kamridah; Tangahu, Deybi Agustin (RIWAYAH, 2023)
Sanad is the most important element in a Hadith. Without a sanad, the authenticity of the hadith can be doubted, whether the hadith is from the Prophet or not. In fact, historical records prove that in practice, the sanad system has existed since the time of the Prophet Muhammad. However, entering the modern era, studies and criticisms of the theory of sanad are ample. In fact, this theory tends to be considered not to be used as a benchmark in determining the authenticity of a hadith, because it is considered to still have weaknesses. Based on this background, this paper aims to analyze the theory of sanad in the epistemological aspect. Some of the issues to be discussed in this research are discourses related to the concept of sanad, methodology of sanad and the authenticity value of sanad. The author focuses on these three main points, because they are the essence of epistemological issues. Thus, this paper is expected to provide an overview regarding the nature of sanad, its concepts and methodologies which are benchmarks in determining the validity, authenticity and historicity of a hadith.[Sanad merupakan unsur terpenting dalam sebuah hadis. Tanpa adanya sanad, maka keabsahan hadis dapat diragukan, apakah hadis tersebut berasal dari Nabi atau bukan. Faktanya, catatan sejarah membuktikan bahwa dalam praktiknya, sistem sanad sudah ada sejak zaman Nabi Muhammad SAW. Namun memasuki era modern, kajian dan kritik terhadap teori sanad sudah banyak. Faktanya, teori ini cenderung dianggap tidak bisa dijadikan tolak ukur dalam menentukan keabsahan suatu hadis, karena dianggap masih memiliki kelemahan. Berdasarkan latar belakang tersebut, maka tulisan ini bertujuan untuk menganalisis teori sanad dalam aspek epistemologis. Beberapa permasalahan yang akan dibahas dalam penelitian ini adalah wacana terkait konsep sanad, metodologi sanad dan nilai keaslian sanad. Penulis memusatkan perhatian pada ketiga pokok bahasan tersebut, karena merupakan inti permasalahan epistemologis. Dengan demikian, tulisan ini diharapkan dapat memberikan gambaran mengenai hakikat sanad, konsep dan metodologinya yang menjadi tolok ukur dalam menentukan keabsahan, kesahihan, dan historisitas suatu hadis.]